Improved Linear Combination of Two Estimators for a Function of Interested Parameter (2016)
In this paper, we consider the problem of improving the efficiency of alinear combination of two estimators, when the population coefficient of variation is known. We generalized the discussion from the case of a parameter to a function of interested parameter. We show that two estimators obtained from improved linear combination of two estimators and linear combination of two improved estimators are equivalent, in terms of efficiency. We also show that, how one can construct an doubly-improved linear combination of two estimators, when the population coefficient of variation is known.